Black webfeminism: resistance narratives - Silva, Célia Regina (Revista Hipótese, 2016)
Since the second half of the twentieth century, social movements and collective action have qualified and diversified in organizational networks that go beyond traditional models of narrative. This article presents theories of Information and Communication Technologies (ICT) and its intersection with gender and race issues. The appropriation of technology gives them social role of mediators, contributing to the construction of media visibility models. Successive level of cultural expressions on most often encountered in the peripheries, these new models pervade technological experiences in representation processes, producing positive narratives of blackness women, leading to new models of visual poetics ensnared by engagement. The result of these networks is that they, through the media, especially the Internet, can overcome local, national and international boundaries, and are able to give visibility to racism theme, sexism, education, human rights, respect the differences.
Keywords: Black women; Feminism; ICT; Visual poetics; Identity